Pia Desideria - Spener, Philipp Jakob (Fortress Press, 1996)
Spener presented a six-point plan for bringing reforming the church, which would lead to continuing reformation in many ways. The first of these was a rededication and refocus upon scripture (which might seem a bit strange coming from a sola-scriptura early Lutheran, that this should be a need). The second was the idea of the priesthood of all believers, which did not in Spener`s view supplant the ordained clerical roles, but would extend the obligations and graces of the priesthood upon the whole community. The third was an understanding that Christianity was not just a statement or system of beliefs, but a practice and way of life. The fourth was the avoidance of religious controversies (often the hope but rarely the realisation of those who are reformers). The fifth is a placing a value on education, particularly for the clergy. The sixth is the proper use and exercise of preaching, which involves pastoral, prophetic, and teaching aspects.